Adoption of yam minisett technology by women farmers in Abia State, Nigeria - Ironkwe, A.; Asiedu, Robert; Unamma, R.P. (African Journals Online, 2007)
The study was designed to determine the adoption of yam minisett technology by omen farmers in Abia state in 2004. This was with a view to determining how best to accelerate the adoption of the technology in the state. A multi-stage random sampling technique was used by selected 234 yam growing women farmers from the three agricultural zones of the state interview schedule was used to collect primary data from the respondents.